2012
DOI: 10.1177/0961203312465779
|View full text |Cite
|
Sign up to set email alerts
|

MicroRNA-101, mitogen-activated protein kinases and mitogen-activated protein kinases phosphatase-1 in systemic lupus erythematosus

Abstract: Systemic lupus erythematosus (SLE) is the prototype of human autoimmune disease in which various inflammatory cytokines such as tumor necrosis factor-alpha (TNF-α), interleukin (IL)-1, IL-6 and interferon (IFN) play crucial pathogenic roles. The production of these cytokines is responsible for the mitogen-activated protein kinases (MAPKs), which can also generate mitogen-activated protein kinases phosphatases (MKPs). MKP-1, a prototypical member of the MKP family that can influence outcomes of autoimmune disea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
15
0

Year Published

2014
2014
2025
2025

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(15 citation statements)
references
References 43 publications
0
15
0
Order By: Relevance
“…17,18 Previous studies demonstrated that expression of miR-101a is modulated by the PI3K/Akt signaling pathway, which is activated in response to IL-1β. 19,20 Wei et al 21 have demonstrated that miR-30b is positively regulated by NF-κB. Therefore, we believe that IL-1β alone is capable of inducing alterations in miR-101a and miR-30b expression, and that IL-1β-mediated signaling pathways participate in the induction of miR-101a and miR-30b in β-cells, though the latter hypothesis requires further investigation.…”
Section: Discussionmentioning
confidence: 75%
“…17,18 Previous studies demonstrated that expression of miR-101a is modulated by the PI3K/Akt signaling pathway, which is activated in response to IL-1β. 19,20 Wei et al 21 have demonstrated that miR-30b is positively regulated by NF-κB. Therefore, we believe that IL-1β alone is capable of inducing alterations in miR-101a and miR-30b expression, and that IL-1β-mediated signaling pathways participate in the induction of miR-101a and miR-30b in β-cells, though the latter hypothesis requires further investigation.…”
Section: Discussionmentioning
confidence: 75%
“…KEGG analysis suggests that seven of nine genes of the MAPK signaling pathway are target genes of miRNA-101-3p: CACNB2, DUSP1, FOS, NLK, RAC1, RAP1B and TGFBR1. Regulation of the miR-101/MAPK pathway plays an important role in proliferation and metastasis of gallbladder carcinoma [47], in LPS-activated Cellular Physiology and Biochemistry Cellular Physiology and Biochemistry macrophages [48], in systemic lupus erythematosus [49] and in proliferation and migration of cardiac fibroblast [50]. Wang et al found that inhibition of miR-101could attenuate H9C2 apoptosis induced by hydrogen peroxide [41].…”
Section: Discussionmentioning
confidence: 99%
“…A number of studies have indicated that miR-101 is involved in a variety of diseases [ 40 , 41 , 42 , 43 , 44 ]. Recently, we investigated the miRNA expression profiling in the MG-infected lungs vs. the non-infected lungs of specific-pathogen-free (SPF) chicken embryos by Solexa deep sequencing (lab unpublished data).…”
Section: Introductionmentioning
confidence: 99%